Legal regulation of drinking water (Journal of actual problems of jurisprudence, 2018)
In article legal regulation of potable water in Republic Kazakhstan is considered. Condition and quality of water resources in Republic Kazakhstan. Definitions of the general parameters of potable water. Questions on a security of potable water. Ways of elimination of deficiency of fresh water to Republic Kazakhstan.Key words: drinking water; fresh water; shortage of fresh water; water resources; technical regulations for drinking water.